Effectiveness of a web-based behavioural activation intervention for individuals with depression based on the Health Action Process Approach: protocol for a randomised controlled trial with a 6-month follow-up. Issue 1 (24th January 2022) - Krämer, Lena Violetta; Mueller-Weinitschke, Claudia; Zeiss, Tina; Baumeister, Harald; Ebert, David Daniel; Bengel, Jürgen
Abstract : Introduction: Behavioural activation is a highly effective treatment for depression. However, there is considerable heterogeneity of interventions grouped under the term 'behavioural activation'. A main reason for the heterogeneity is the lack of a unified theory in the intervention development: few of the established intervention manuals give a theoretical rationale for their intervention techniques. For the first time, this study will examine the effectiveness of a theory-based behavioural activation intervention ( InterAKTIV ) based on the Health Action Process Approach. The intervention is implemented online to ensure broad dissemination and standardisation. Methods and analysis: In a two-arm randomised controlled trial, the effectiveness of a guided web-based behavioural activation intervention for people with depression will be evaluated. Participants are recruited via the print and online media of a large German healthcare insurance company. Individuals (age 18–65), who meet criteria for major depressive episode in a clinical interview and no exclusion criteria are eligible for inclusion. A target sample of 128 participants is randomly allocated to either the intervention group (immediate access to InterAKTIV ) or treatment as usual (access after follow-up assessment). The primary outcome of depressive symptom severity (Quick Inventory of Depressive Symptomatology Clinician Rating) and secondary outcomes, including behavioural activation, physical activity and motivational and volitional outcomes are assessed at baseline, post treatment and 6-month follow-up. Data will be analysed on an intention-to-treat basis with additional per-protocol analyses. Ethics and dissemination: This trial is approved by the ethics committee of the Albert-Ludwigs-University of Freiburg (no.: 20-1045). All participants are required to submit their informed consent online before study inclusion. The results will be submitted for publication in a peer-reviewed journal and presented at conferences. Trial registration number: This trial was registered in the German Clinical Trials Register (DRKS): DRKS00024349 (date of registration: 29 January 2021).